Crack growth simulation in heterogeneous material by S-FEM and comparison with experiments (Fracture and Structural Integrity, 2015)
Fully automatic fatigue crack growth simulation system is developed using S-version FEM (SFEM).This system is extended to fracture in heterogeneous material. In the heterogeneous material, crack tipstress field becomes mixed mode condition, and crack growth path is affected by inhomogeneous materials and mixed mode conditions. Stress Intensity Factors (SIF) in mixed mode condition are evaluated using VirtualCrack Closure Method (VCCM). Criteria for crack growth amount and crack growth path are used based on these SIFs, and growing crack configurations are obtained.Three crack growth problems are simulated. One is crack growth in bi-materila made of CFRP plate andAluminum alloy. Initial crack is located in CFRP plate, and grows toward Aluminum alloy. Crack growingdirection changes and results are compared with experimental one. Second problem is crack growth in bimaterial made of PMMA and Aluminum alloy. Initial crack is located in PMMA plate and parallel to phaseboundary. By cahnging loading conditions, several cases are simulated and compared with experimental ones.In the experiment, crack grows into phase boundary and grow along it. This case is simulated precisely, and theeffect of pahse boundary is discussed. Last case is Stress Corrosion Cracking (SCC) at Hot-Leg Safe-End ofPressurized Water Rreactor. This location is made of many kinds of steels by welding. In some steel, SCC doesnot occur and in other steel, SCC is accelerated. As a result, small surface crack grows in complicated manner.
Keywords: Heterogeneous Material